1995
DOI: 10.1111/j.1365-2222.1995.tb03256.x
|View full text |Cite
|
Sign up to set email alerts
|

Local nasal immunotherapy for birch allergic rhinitis with extract in powder form

Abstract: This study indicates that LNIT with allergen in powder form has proven clinically effective in the treatment of birch allergic rhinitis. Further studies are needed to establish whether this treatment can be considered a real alternative to the traditional subcutaneous immunotherapy in birch allergic rhinitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…So far, 21 studies are available for LNIT, and 14 of them were properly performed (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), Of these, 13 report a significant improvement of rhinitic symptoms. Furthermore, a reduction of the nasal reactivity and local immunologic response was found in some studies, while systemic immunologic changes were usually absent or equivocal: this may suggest that LNIT exerts its actions only on the target organ.…”
Section: Experimental Evidence: Clinical Efficacymentioning
confidence: 99%
“…So far, 21 studies are available for LNIT, and 14 of them were properly performed (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56), Of these, 13 report a significant improvement of rhinitic symptoms. Furthermore, a reduction of the nasal reactivity and local immunologic response was found in some studies, while systemic immunologic changes were usually absent or equivocal: this may suggest that LNIT exerts its actions only on the target organ.…”
Section: Experimental Evidence: Clinical Efficacymentioning
confidence: 99%
“…Allergen-specific IT is the only treatment recognized to be effective. It has been shown to prevent new sensitization, and the clinical efficacy of various specific nasal ITs has been documented either using aqueous extract (22,23) or extract in powder form (26,27). However, persistent local reaction and technical difficulty limit its application.…”
Section: Discussionmentioning
confidence: 99%
“…Four studies (312)(313)(314)(315) could not be used because of methodological limitations (Table 12). Thirteen out of 14 studies found a significant improvement of nasal symptoms both in perennial (1 study) and seasonal allergic rhinitis (12 studies) (316)(317)(318)(319)(320)(321)(322)(323)(324)(325)(326)(327)(328)(329). In general, the effectiveness of nasal immunotherapy seems to be dose-related, and clinical improvement appears to have been greater with aqueous and powdered vaccines than with modified ones.…”
Section: Nasal Routementioning
confidence: 99%